Peningkatan Kemampuan Membaca Nyaring dengan Menggunakan Buku Cerita Bergambar Siswa kelas II SD Negeri 1 Watampone - Mardiana, Dian Bone Asturi (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
This research is a PTK research that aims to describe the improvement of students' ability to read aloud by using picture storybooks of grade II students of SD Negeri 1 Watampone. The subjects of this study were all second grade students of SD Negeri 1 Watampone, totaling 31 students and the second grade homeroom teacher. This research setting took place at SD Negeri 1 Watampone. Data collection techniques using observation and tests. Data analysis techniques are reducing data, describing data, and drawing conclusions. The results showed that in cycle I as many as 64.51% or 20 students obtained an average score of 65.32% in the sufficient category (C) and increased in cycle II as many as 77.41% or 24 students with an average score of 73.58% in the good category (B). The conclusion of this study is that using picture storybooks can improve the ability to read aloud of grade II students of SD Negeri 1Watampone.